2015
DOI: 10.1016/j.jphs.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and pharmacological characteristics of bortezomib-induced peripheral neuropathy in rats

Abstract: Bortezomib, an effective anticancer drug for multiple myeloma, often causes peripheral neuropathy which is mainly characterized by numbness and painful paresthesia. Nevertheless, there is no effective strategy to escape or treat bortezomib-induced peripheral neuropathy (BIPN), because we have understood few mechanism of this side effect. In this study, we evaluated behavioral and pathological characteristics of BIPN, and investigated pharmacological efficacy of various analgesic drugs and adjuvants on mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…Existing models of BIPN have also reported mechanical hypersensitivity due to bortezomib dosing, but in a shorter-lasting manner, 29 days (0.2 mg·kg À1 bortezomib; Yamamoto et al, 2015) and 54 days (0.2 mg·kg À1 Velcade; Robinson et al, 2014), compared to~80 days in our investigation. Dosing with bortezomib has also previously been shown to induce cold allodynia at days 11 and 15 (Zheng et al, 2012;Yamamoto et al, 2015), whereas Velcade® administration was not associated with development of cold allodynia following four doses at 0.15 mg·kg À1 (Robinson et al, 2014). In conjunction with long-lasting mechanical hypersensitivity, we found evidence of a short-lasting cold allodynia resulting from four doses of 0.2 mg·kg À1 Velcade®, evident at day 14 only.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Existing models of BIPN have also reported mechanical hypersensitivity due to bortezomib dosing, but in a shorter-lasting manner, 29 days (0.2 mg·kg À1 bortezomib; Yamamoto et al, 2015) and 54 days (0.2 mg·kg À1 Velcade; Robinson et al, 2014), compared to~80 days in our investigation. Dosing with bortezomib has also previously been shown to induce cold allodynia at days 11 and 15 (Zheng et al, 2012;Yamamoto et al, 2015), whereas Velcade® administration was not associated with development of cold allodynia following four doses at 0.15 mg·kg À1 (Robinson et al, 2014). In conjunction with long-lasting mechanical hypersensitivity, we found evidence of a short-lasting cold allodynia resulting from four doses of 0.2 mg·kg À1 Velcade®, evident at day 14 only.…”
Section: Discussionsupporting
confidence: 45%
“…The model characterized in this study did not find loss of motor function or reduced axon myelination and IENF crossings in bortezomib‐treated animals compared to vehicle‐treated controls. Previous studies have identified degeneration of myelinated sciatic nerve fibres following the same dosing regimen (albeit using non‐Velcade® bortezomib) used in this study, but an absence of ATF3‐positive staining (Yamamoto et al, ). Another investigation has reported, but did not quantify, ATF3‐positive staining in the DRG following bortezomib administration following a significantly higher cumulative dose of 6.4 mg·kg −1 (Carozzi et al, ).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The preventive effect of fulvestrant against mechanical allodynia appears to be associated with its protective effect against neuronal damage. Indeed, we observed a significant alteration in the circularity of the sciatic nerve (a parameter of axonal degeneration 17,18 ) in oxaliplatin-treated rats, and nerve damage and mechanical allodynia have been reported to concurrently occur in oxaliplatin-treated rats. 5 However, it has also been reported that axonal degeneration (e.g., axonal diameter and fibre area) of the sciatic nerve is not observed in oxaliplatin-treated rats.…”
Section: Discussionmentioning
confidence: 74%
“…a ). Quantitative analysis revealed that an oxaliplatin‐induced decrease in the circularity of fibres, an index of axonal degeneration, was not observed in the sciatic nerve of oxaliplatin‐treated rats that were also treated with fulvestrant (Fig. b ).…”
Section: Resultsmentioning
confidence: 99%